The Contextual Effect of School on the Premarital Sex among Adolescents in Bantul, Yogyakarta - Galuh Tunjung Pertiwi; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2018)
Background: Previous studies have identified individual and school‐level characteristics that are associated with sexual risk‐taking. But similar studies in Indonesia is lacking. This study aimed to examine the contextual effect of school on the premarital sex among adolescents in Bantul, Yogyakarta.Subjects and Method: This was a cross-sectional study carried out at 25 senior high schools in Bantul, Yogyakarta, from November to December 2018. A sample of 225 adolescents aged 15-18 years was selected by stratified random sampling. The dependent variable was premarital sex. The independent variables were the intention, subjective norm, perceived behavior control, family intimacy, and peer group. The data were collected by questionnaire and analyzed by a multilevel logistic regression on Stata 13.Results: Premarital sex incrased with favorable intention (b= 2.70; 95% CI= 0.50 to 3.15; p= 0.007), subjective norm (b= 4.66; 95% CI= 1.89 to 4.63; p<0.001), and suitable peer group (b= 4.34; 95% CI= 1.99 to 5.28; p<0.001). Premarital sex decreased with positive attitude (b= -4.31; 95% CI= -4.15 to -1.55; p<0.001), strong perceived behavior control (b= -2.37; 95% CI= -2.53 to -0.23; p=0.018), and strong family intimacy (b= -2.44; 95% CI= -2.69 to 0.29; p=0.015). There was contextual effect of school on premarital sex with ICC= 63.72%.Conclusion: Premarital sex increases with favorable intention, subjective norm, and suitable peer group. Premarital sex decreases with positive attitude, strong perceived behavior control, and strong family intimacy. There is a contextual effect of school on premarital sex, which calls for attention.Keywords: premarital sex, school, multilevel analysisCorrespondence: Galuh Tunjung Pertiwi. Masters Program in Public Health, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: galuhpertiwi2017@gmail.com. Mobile: +6281229722373.Journal of Health Promotion and Behavior (2018), 3(4): 240-247https://doi.org/10.26911/thejhpb.2018.03.04.03